Towards Sustainable Hilsa Fish (Tenualosa ilisha) Management in Labuhanbatu Regency, North Sumatra, Indonesia: SWOT Analysis and Community Participation - Rumondang Rumondang; Heru Gunawan; Muhammad Sabir Ramadhan; Syafrida Br Tambunan; Nurhadi Nurhadi; Abdul Ghofur; Dwi Arditiana (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research 1. The study applies the Rational, Analytical, and Holistic Strategic Governance (RAHSG) framework to Indonesian hilsa fisheries. 2. Survey reveals that 80% of coastal residents support conservation policies and value the hilsa’s ecological role. 3. SWOT analysis positions the Labuhanbatu hilsa fishery in a favorable growth quadrant for proactive management. 4. Results identify institutional fragmentation and limited population data as the primary barriers to sustainable governance.   Abstract Hilsa Fish (Tenualosa ilisha), despite its ecological and socio-economic importance in Labuhanbatu, Indonesia, is experiencing population decline due to overexploitation and habitat degradation, highlighting a critical need for management strategies. This study aims to analyze coastal community perceptions and participation in the management of hilsa fish and to formulate sustainable management strategies using Rational, Analytical, and Holistic Strategic Governance (RAHSG) framework and Strength, Weakness, Opportunity, Threat (SWOT) analysis in Labuhanbatu Regency. The RAHSG framework was used to structure the rational evaluation of governance evidence, integrate SWOT factor weighting, and support holistic interpretation in developing management strategies. The research used a descriptive method with quantitative and qualitative approaches through a questionnaire survey involving 100 proportionally selected respondents. Data were analyzed using the Likert scale and SWOT analysis. The results indicate that community perceptions of the ecological and economic value of hilsa fish are categorized as good to excellent, with more than 80% of respondents supporting conservation policies. The SWOT analysis yielded an internal factor score of 1.04 and an external factor score of 1.25, positioning hilsa fish management in Quadrant I (Aggressive Strategy). Key strengths identified include established formal regulations and well-known migration routes, while the primary weaknesses are limited population data and weak institutional coordination. This strategic position suggests that current healthy habitat conditions and cross-sector opportunities can be leveraged to mitigate threats from fishing pressure and migration route disruption. The study concludes that an integrated, participatory management approach is essential, focusing on interagency collaboration and the establishment of formal conservation zones. This aggressive strategy should prioritize community empowerment to sustain existing support. Future research should examine the institutional power dynamics and stakeholder cooperative behaviors required to scale this co-management model effectively.